Synthesis, Characterization and Corrosion Protective Efficiency of 2[2-Oxo-phenyl hydrazinyl ethyl] benzamide on Mild Steel in Sulphuric Acid Medium - Rinki Goel; Weqar A. Siddiqi; V. M. Chaubey; Bahar Ahmed (E-Journal of Chemistry)
2[2-Oxo-phenyl hydrazinyl ether] benzamide (2BA) was synthesized, characterized and tested effective for corrosion inhibition of mild steel in 1 N H2SO4 solution using galvanodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. Polarization resistances calculated from the EIS measurements are in good agreement with those obtained from alternating current (AC) polarization measurements. The mild steel samples were also analyzed by Scanning Electron Microscopy (SEM). The result showed that 2BA is an excellent inhibitor for mild steel in acid medium. The inhibition was assumed to occur via adsorption of the inhibitor molecule on the metal surface. In the 303-323K temperature range, the 2BA adsorption follows Langmuir isotherm model. The protection efficiency increases with increasing the inhibitor concentration in the range of 250-1000 ppm but slightly decreases with increasing temperature.